PENGEMBANGAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS I SD NEGERI PULOGEDE 1 - Siti Rohmah; Ina Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Research conducted on mathematics education at SD Negeri Pulogede 1 shows that the implementation of learning is not optimal. Student learning outcomes have not reached the KKTP. The purpose of this study was to improve student learning outcomes by using animated video media. Specifically, this study aims to determine the validity, practicality, and effectiveness of animated video media on student learning outcomes. This research was conducted at SDN Pulogede 1. The data source consisted of 11 first grade students of SDN Pulogede 1. This research is research and development (R&D). The findings of this study indicate an increase in learning outcomes of first grade students at SDN Pulogede 1, which is indicated by an increase in practical skills and cognitive outcomes. This improvement was achieved through the integration of animated video media in the learning process. The final results showed that 100% of students achieved mastery in the second cycle. Animated video media can provide real-life experiences that can foster independent learning activities among students.